(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the fungitoxic efficacy of Vernonia amygdalina (bitter leaf) and Cymbopogon citratus (lemon grass) extracts against Fusarium proliferatum, a significant pathogen affecting rice production. Treatments comprised of 2 plants (bitter leaf and lemongrass) extracted using 2 methods (Soxhlet and Maceration) at 4 concentrations (0%, 50%, 75%, and 100%) respectively to assess their inhibitory effects on fungal radial growth over a 7-day period. The experiment employed a 2 × 2 × 4 factorial laid in a completely randomized design with three replications. Analysis of variance revealed significant main effects (p<0.05) for plant type, extraction method, concentration, and interactions between all factors in controlling F. proliferatum growth. Results showed that lemongrass extract exhibited superior antifungal activity compared to bitter leaf, with maximum inhibition of 39.88% observed on day 4. Soxhlet extraction proved more effective than maceration, particularly in maintaining consistent inhibition rates during later stages of observation. A clear concentration-dependent response was observed, with 100% concentration showing the highest inhibition rates (50.62 - 63.93%). The interaction between extraction methods and plant types revealed that Soxhlet-extracted lemongrass provided the most stable and sustained antifungal activity. While macerated bitter leaf showed high initial inhibition (69.74% on day 2), its efficacy declined substantially over time. The study suggested that lemongrass extracted via the Soxhlet method represents a promising natural alternative for controlling F. proliferatum in rice production systems, particularly when applied at one hundred percent. These findings contribute to the development of sustainable disease management strategies in rice cultivation.